Developing Red-White Monopoly Games through Integrative Thematic Learning in the Primary School - Nilam Sri Anggraheni; Nurul Hidayah; Ayu Nur Shawmi (Al Ibtida: Jurnal Pendidikan Guru MI, 2019)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  AbstractPlaying is a fun activity and liked by children. It can be used as a media of learning. The observations carried out in SD Negeri 3 Sawah Lama Bandar Lampung found that the learning media used was not interesting for students to learn. The aims of the study are to determine the steps in developing a game of red-and-white monopoly media;to know the quality of red-and-white monopoly games; and to find out the responses of students to the red-and-white monopoly game. This study is a research anddevelopment (R & D) using the Borg and Gall model. The steps start from exploring potential aspect and its problems, data collection, product design, design validation, design revision, product testing, and product revision. The techniques of data collection are observations, interviews, and questionnaires.The data analysis technique uses is qualitative descriptive. The results of the analysis show that the assessment of material experts gained an average of 93% "very good",the assessment of media experts gained an average of 92% "very good", the assessment of education practitioners gained an average of 90% "very good". While the questionnaire responses of students in the small class trials gained an average of 96% "very good" andthe results of a large class trial gained an average of 94% "very good". Based on the results of the description above, the products developed by researchers are feasible to be used as learning media.Keywords: media, monopoly games, integrative thematic learningAbstrakBermain merupakan kegiatan yang menyenangkan dan disukai oleh anak-anak. Bermain juga dapat digunakan sebagai media dalam pembelajaran. Hasil observasi yang dilakukan di SD Negeri 3 Sawah Lama Bandar Lampung didapati bahwa bentuk media pembelajaran yang digunakan tidak menarik peserta didik untuk belajar. Penelitian ini bertujuan untuk mengembangkan media permainan monopoli merah-putih, mengetahui kualitas media permainan monopoli merah-putih, dan untuk mengetahui respon peserta didik terhadap media permainan monopoli merah-putih. Penelitian ini merupakan penelitian pengembangan (R&D) dengan menggunakan model Borg dan Gall. Langkah-langkahnya dimulai dari menggali potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk, dan revisi produk. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan angket. Teknik analisis data yang digunakan adalah deskriptif kualitatif.Â  Hasil penelitian menunjukkan bahwa penilaian ahli materi memperoleh rata-rata 93% â€œsangat baikâ€, penilaian ahli media memperoleh rata-rata 92% â€œsangat baikâ€, penilaian praktisi pendidikan memperoleh rata-rata 90% â€œsangat baikâ€. Sementara itu, respon peserta didik pada uji coba kelas kecil memperoleh rata-rata 96% â€œsangat baikâ€, dan hasil uji coba kelas besar memperoleh rata-rata 94% â€œsangat baikâ€. Berdasarkan hasil uraian di atas, maka produk yang dikembangkan oleh peneliti layak untuk digunakan sebagai media pembelajaran.Kata kunci: media, permainan monopoli, pembelajaran tematik integratif